Newsletter No. 7 - (:unkn) unknown (My University, 2004)
Progress on the main data collection including reports on remote areas, Indigenous respondents, response rates, completion of time use diaries, data access, a FaCS workshop to develop a long-term research program, and Wave 2 developments.
7
Newsletter
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology